Three-dimensional Imaging, Visualization, and Display - Javidi, Bahram; Okano, Fumio; Son, Jung-Young.; SpringerLink (Online service) (New York, NY : Springer US, 2009)
Three-Dimensional Imaging, Visualization, and Display describes recent developments, as well as the prospects and challenges facing 3D imaging, visualization, and display systems and devices. With the rapid advances in electronics, hardware, and software, 3D imaging techniques can now be implemented with commercially available components and can be used for many applications. This volume discusses the state-of-the-art in 3D display and visualization technologies, including binocular, multi-view, holographic, and image reproduction and capture techniques. It also covers 3D optical systems, 3D display instruments, 3D imaging applications, and details several attractive methods for producing 3D moving pictures. This book integrates the background material with new advances and applications in the field, and the available online supplement will include full color videos of 3D display systems. Three-Dimensional Imaging, Visualization, and Display is suitable for electrical engineers, computer scientists, optical engineers, physicists, graduate students, government and industry technology managers, as well as anyone with an interest in this exciting future technology.
3-D Image Display and Generation Techniques Based on I.P -- Three-Dimensional Integral Television Using High-Resolution Video System with 2000 Scanning Lines -- High Depth-of-Focus Integral Imaging with Asymmetric Phase Masks -- Integral Imaging Using Multiple Display Devices -- 3-D to 2-D Convertible Displays Using Liquid Crystal Devices -- Effect of Pickup Position Uncertainty in Three-Dimensional Computational Integral Imaging -- 3-D Image Reconstruction with Elemental Images Printed on Paper -- Multiview Image Acquisition, Processing and Display -- Viewing Zones of IP and Other Multi-view Image Methods -- Rich Media Services for T-DMB: 3-D Video and 3-D Data Applications -- Depth Map Generation for 3-D TV: Importance of Edge and Boundary Information -- Large Stereoscopic LED Display by Use of a Parallax Barrier -- Synthesizing 3-D Images with Voxels -- Multi-view Image Acquisition and Display -- 3-D Video Processing for 3-D TV -- 3-D Image Acquisition, Processing and Display Based on Digital Holography -- Imaging 3-D Objects by Extending the Depth of Focus in Digital Holography -- Extraction of Three-dimensional Information from Reconstructions of In-Line Digital Holograms -- Polarimetric Imaging of 3-D Object by Use of Wavefront-Splitting Phase-Shifting Digital Holography -- Three-dimensional Display with Data Manipulation based on Digital Holography -- Other 3-D Image Acquisition and Display Techniques, and Human Factors -- A 3-D Display System Using Motion Parallax -- Dynamic Three-Dimensional Human Model -- Electronic Holography for Real Objects Using Integral Photography -- Working Towards Developing Human Harmonic Stereoscopic Systems -- Development of Time-Multiplexed Autostereoscopic Display Based on LCD Panel -- 3-D Nano Object Recognition by Use of Phase Sensitive Scatterometry.
Keywords: PHYSICS; COMPUTER VISION; PHYSICS; OPTICS, OPTOELECTRONICS, PLASMONICS AND OPTICAL DEVICES; IMAGE PROCESSING AND COMPUTER VISION; SIGNAL, IMAGE AND SPEECH PROCESSING